Pengaruh Pengetahuan Perpajakan, Kesadaran Wajib Pajak, Dan Sikap Wajib Pajak Terhadap Kepatuhan Wajib Pajak Bumi Dan Bangunan Di Desa Mlandangan, Kecamatan Pace, Kabupaten Nganjuk - Candra, Nadyla Alfiena; Solikah, Mar’atus; Tohari, Amin (CV. SINAR HOWUHOWU, 2025)
revenue for local development, yet it faces challenges in taxpayer compliance. In Mlandangan Village, this issue arises due to a lack of understanding, low awareness, and negative attitudes of the community towards PBB, often because of insufficient socialization of its benefits and issues of trust in fund management. The objective of this research is to analyze the influence of tax knowledge, taxpayer awareness, and taxpayer attitudes on PBB compliance. Using a quantitative approach with 95 respondents in Mlandangan Village, data was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Research findings indicate that: Tax knowledge has a positive and significant influence on PBB compliance (path coefficient = 0.719; p-value = 0.000), emphasizing the importance of understanding.Taxpayer awareness has a negative and significant influence on PBB compliance (path coefficient = -0.535; p-value = 0.008). This finding is interesting and indicates that increased awareness might be accompanied by a perception of high tax burden or dissatisfaction with fund transparency. Taxpayer attitude has a positive and significant influence on PBB compliance (path coefficient = 0.615; p-value = 0.004), demonstrating the important role of a positive attitude.Overall, the model is strong, explaining 67.4% of the variation in PBB compliance.Suggestions from this research are divided, for future research: It is recommended to delve deeper into the negative influence of taxpayer awareness through mixed methods and to test mediating/moderating variables such as trust in government and for tax offices: It is necessary to optimize PBB education and socialization with better materials and a focus on direct benefits, as well as to improve services and transparency in fund management to build positive taxpayer attitudes.